Energy, transport and environment indicators. 2016 edition (Luxembourg, 2016)
"he multi-thematic statistical book Energy, transport and environment indicators comprises a broad set of data collected by Eurostat. It presents the EU’s main indicators for energy, transport and environment that support the design and monitoring of EU policies. The publication provides data for the European Union and its Member States, while some indicators include also data for the EFTA countries and candidate countries and potential candidates to the EU. "